Antiproliferative and biochemical evaluation of rose extracts: impact on tumor and normal skin cells - Faur, Cosmin-Alin; Zăhan, Marius; Bunea, Claudiu Ioan; Hârșan, Eugenia; Bora, Florin-Dumitru; Bunea, Andrea (Frontiers in Plant Science, 2024)
Rose petals (Rosa L.) are rich sources of phenolic compounds, including anthocyanins. Anthocyanins and anthocyanidins are associated with multiple health benefits due to their antioxidant properties. In this study, eighteen rose cultivars were comparatively analyzed to determine their total polyphenol and flavonoid content, as well as their antioxidant activity using the 2,2-diphenylpicrylhydrazyl (DPPH) radical scavenging method. The three cultivars with the highest anthocyanin content were further examined for cytotoxic effects on cell cultures at various extract concentrations (200-1000 µg/mL) using two skin cell lines: a melanoma cell line (A375) and a normal skin cell line (Hs27). The extracts were purified using Amberlite XAD-7 and Sephadex LH-20 columns to obtain anthocyanin-rich fractions. Individual anthocyanins were separated and identified using high-performance liquid chromatography coupled with electrospray ionization mass spectrometry (HPLC-ESI-MS). The HPLC-MS analysis identified nine different anthocyanin compounds, with the total anthocyanin content in the rose cultivars varying from 12.42 to 331.95 mg of cyanidin-3-glucoside equivalent/100g of fresh weight. The total polyphenol and total flavonoid contents ranged from 289 to 2703 mg gallic acid equivalent/100g fresh weight and 102 to 603 mg catechin equivalent/100g fresh weight, respectively. Antioxidant activity ranged from 450 to 1304 µmol trolox equivalent/g fresh weight. A significant correlation was observed between antioxidant activity and the content of anthocyanins (R = 0.875, p < 0.001), flavonoids (R = 0.982, p < 0.001), and polyphenols (R = 0.991, p < 0.001). Furthermore, principal component analysis, along with dendrograms and heatmaps, illustrated the relationships among these key compounds and their association with antioxidant activity. The MTT assay showed a substantial suppression of A375 cancer skin cells, while simultaneously exhibiting cell proliferation in Hs27 normal skin cells in a concentration-dependent manner. Altogether, results suggest that the anthocyanins from these rose cultivars could be considered as a promising agent for adjuvant treatment of skin melanoma.